How do elite ski jumpers handle the dynamic conditions in imitation jumps? - Ettema, G.; Hooiveld, J.; Braaten, S.; Bobbert, M. (Journal of Sports Sciences, 2016)
We examined the effect of boundary conditions in imitation ski jumping on movement dynamics and coordination. We compared imitation ski jumps with - and without - the possibility to generate shear propulsion forces. Six elite ski jumpers performed imitation jumps by jumping from a fixed surface and from a rolling platform. The ground reaction force vector, kinematics of body segments, and EMG of eight lower limb muscles were recorded. Net joint dynamics were calculated using inverse dynamics. The two imitation jumps differed considerably from each other with regard to the dynamics (moments, forces), whereas the kinematics were very similar. Knee power was higher and hip power was lower on the rolling platform than on the fixed surface. Mean EMG levels were very similar for both conditions, but differences in the development of muscle activity were indicated for seven of eight muscles. These differences are reflected in a subtle difference of the alignment of ground reaction force with centre of mass: the ground reaction force runs continuously close to but behind the centre of mass on the rolling platform and fluctuates around it on the fixed surface. This likely reflects a different strategy for controlling angular momentum.